2002
DOI: 10.1161/01.cir.0000014684.75359.68
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen Genotype Affects Renal and Adrenal Responses to Angiotensin II in Essential Hypertension

Abstract: Background — Renovascular and adrenal responses to infused angiotensin II (Ang II) are intermediate phenotypes that may indirectly reflect tissue renin-angiotensin system activity. We examine herein angiotensinogen ( AGT ) as a candidate gene to help elucidate potential mechanisms for previously reported AGT linkage and association studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 43 publications
3
38
0
1
Order By: Relevance
“…141,142 One group 143 reported more rapid progression to end-stage renal disease in diabetics with the 235T variant while another did not. 144 Consistent with the notion that the Ϫ6A (or 235T) allele of AGT results in increased tissue expression of angiotensinogen, we found that both normotensive homozygous carriers of the 235T AGT variant (most with a positive family history of hypertension) 145 and hypertensive patients with the Ϫ6AA genotype 146 showed significant blunting of renal vascular response to infused angiotensin II. This blunting (less than usual reduction of renal blood flow in response to infused angiotensin II on a high salt diet) is presumably the result of higher intrarenal angiotensin II production resulting in downregulation of vascular angiotensin II receptors.…”
Section: Autosomal Recessivesupporting
confidence: 84%
See 1 more Smart Citation
“…141,142 One group 143 reported more rapid progression to end-stage renal disease in diabetics with the 235T variant while another did not. 144 Consistent with the notion that the Ϫ6A (or 235T) allele of AGT results in increased tissue expression of angiotensinogen, we found that both normotensive homozygous carriers of the 235T AGT variant (most with a positive family history of hypertension) 145 and hypertensive patients with the Ϫ6AA genotype 146 showed significant blunting of renal vascular response to infused angiotensin II. This blunting (less than usual reduction of renal blood flow in response to infused angiotensin II on a high salt diet) is presumably the result of higher intrarenal angiotensin II production resulting in downregulation of vascular angiotensin II receptors.…”
Section: Autosomal Recessivesupporting
confidence: 84%
“…There was also blunting of the normal stimulation of adrenal aldosterone production by infused angiotensin II on a low salt diet in hypertensive patients with the AGT Ϫ6AA genotype. 146 Interestingly, there was no association between AGT genotype and blood pressure response to salt change in our studies (comparing blood pressures at the end of one week on 200 mEq sodium per day and 1 week on 10 mEq/day) (unpublished observations, 2003). In one study of normotensive and hypertensive persons over age 60, the AGT 235T genotype was associated with a lesser diastolic response to changes in salt intake.…”
Section: Autosomal Recessivementioning
confidence: 58%
“…29 It is of interest that a reduced renal vascular response to exogenous angiotensin II was found among hypertensive carriers of the A(-6) allele, which has been attributed to an effective feedback downregulation of angiotensin II type 1 receptors to any rise in AGT related to A(-6) allele. 30 Altogether, it appears that the genotypic effect of the A(-6) on LVM and LVMI through modulation of AGT levels may be marginal only. Speculatively, it is likely that the variant allele may be a genetic marker reflecting the complex interplay of the RAS genes and that the observed genotypic effect may be caused by linkage disequilibrium with another closely linked polymorphism within the AGT gene or nearby genes.…”
Section: Discussionmentioning
confidence: 98%
“…5 Finally, the angiotensinogen Met235Thr (AGT Met235Thr) polymorphism is of interest because the Thr allele of this polymorphism is associated with high plasma levels of AGT and increased responsiveness to angiotensin II. 6 In addition to studies of angiotensin II and its precursors, many studies have highlighted the importance of endothelium-derived nitric oxide (NO) in inhibiting atherosclerotic disease and the possibility that impairment of endothelial NO production promotes atherosclerosis. NO is produced by endothelial nitric oxide synthase (eNOS).…”
mentioning
confidence: 99%